2019
DOI: 10.1016/j.artd.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of the use of intravenous dexamethasone for postoperative nausea and vomiting in total joint replacement

Abstract: Background Multimodal perioperative pain-management protocols have contributed to the success of elective total joint replacement in orthopedic surgery. General or neuraxial anesthesia for arthroplasty is accompanied by complications such as pruritis, nausea, and vomiting. Dexamethasone has been demonstrated to be a safe perioperative antiemetic. This study evaluates the benefit of low-dose intravenous dexamethasone used in the perioperative period to prevent postoperative nausea and vomiting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The current use of dexamethasone preoperatively, intraoperatively, and postoperatively in diabetic patients undergoing surgery has been to control postoperative nausea, vomiting, and pain, and many studies have revealed a significant correlation between the use of dexamethasone and decreased postoperative pain, nausea, and emesis. [7][8][9][10][11] However, fewer studies have shown no significant correlation between dexamethasone use and effect on the reduction of postoperative nausea and vomiting. [12][13][14] Research studies that track the effect of dexamethasone usage on the control of glucose levels in postoperative diabetic patients are few.…”
Section: Introductionmentioning
confidence: 99%
“…The current use of dexamethasone preoperatively, intraoperatively, and postoperatively in diabetic patients undergoing surgery has been to control postoperative nausea, vomiting, and pain, and many studies have revealed a significant correlation between the use of dexamethasone and decreased postoperative pain, nausea, and emesis. [7][8][9][10][11] However, fewer studies have shown no significant correlation between dexamethasone use and effect on the reduction of postoperative nausea and vomiting. [12][13][14] Research studies that track the effect of dexamethasone usage on the control of glucose levels in postoperative diabetic patients are few.…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41] However, our study found that 10 to 20 mg of intravenous dexamethasone is also effective in preventing PONV. Bustos et al 42 found that two scheduled doses of 8 mg of dexamethasone seemed to be a safe adjunct to the perioperative protocol that reduced PONV. This seems to be in agreement with perioperative intravenous low-dose dexamethasone for prophylactic PONV.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [ 18 ] reported that dexamethasone could significantly reduce the incidence of POV in postoperative and few adverse effects were reported. Bustos et al [ 19 ] found that dexamethasone is a safe adjunct to perioperative protocol that may reduce nausea, thus improving patient satisfaction, and there is an associated reduction in length of stay that may reduce cost of hospitalization. The findings of Moheimani et al [ 20 ] showed that a single preoperative dose of i.v.…”
Section: Discussionmentioning
confidence: 99%